Preseptal cellulitis and cerebral venous sinus thrombosis complication in a patient with diabetes mellitus (Medical Journal of Indonesia, 2022)
This was a rare case of preseptal cellulitis with an unexpected complication by cerebral venous sinus thrombosis. A 73-year-old woman with poorly controlled diabetes mellitus presented with a week history of swelling and redness on the left upper eyelid and right forehead, associated with poor oral intake, lethargy, and fever. She was generally lethargic with poor verbal response. She had cellulitis of the left upper eyelid and right forehead with the left upper eyelid necrosis. Computed tomography venography of the brain revealed thrombosis of the right transverse sinus, right sigmoid sinus, and right internal jugular vein. She later developed left upper eyelid and right forehead abscesses. Incision, drainage, and wound debridement were performed. She was treated with intravenous antibiotics and anticoagulant. After 1 week of treatment, the preseptal and forehead cellulitis had resolved. However, she passed away due to aspiration pneumonia with respiratory failure on day-13 of hospitalization.